Pemanfaatan Limbah Minyak Goreng Bekas dan Bekatul Menjadi Sabun Antiaging - Mita Susanti, Maria; Retno Priamsari, Margareta (Jurnal Farmasi (Journal of Pharmacy), 2019)
Used cooking oil and rice bran is waste that has less economic value. The use of cooking oil repeatedly causes the fatty acids contained in the oil to be more saturated. Changes in the nature of cooking oil make cooking oil unfit for use as food because it can cause health effects on the body. Meanwhile, the availability of rice bran which is very abundant and nutrition of rice bran that contains a high antioxidant has not been comparable with its limited utilization. The research objective is to treat used cooking oil waste and rice bran waste to be processed into anti-aging soap products. This was an experimental research with the independent variable is bran soap formula and the dependent variable is the quality characteristics of bran soap which includes organoleptic test, pH, foam power, free alkali and vitamin E. The data were analyzed descriptively by comparing the results of research with SNI 06-3532 -1994. The results showed rice bran soap that meets the quality requirements is formula II, which is obtained results that meet the soap quality requirements in theory which includes solid organoleptic tests, typical odorous rice bran and brown, pH 11 test, 2,28 cm foam power test, acid test 0,46% free fat, 0,1% free alkaline test and positive contain vitamin E.